HUBUNGAN ASUPAN ENERGI PROTEIN DAN LAMANYA MENJALANI HEMODIALISA DENGAN STATUS GIZI PADA PASIEN GINJAL KRONIK DI RSUD PROF W.Z JOHANNES KUPANG - Benu, Lolang Loriana; Adi, Anak Agung Ayu Mirah (Kupang Journal of Food and Nutrition Research, 2025)
Chronic kidney disease (CKD) is considered a significant health challenge due to its increasing prevalence and poor prognosis. The incidence of chronic kidney disease in East Nusa Tenggara was 0.33% in 2018, while Kupang City had a lower prevalence of 0.45 %, according to Riskesdas. Based on data from the medical records section of RSUD.WZ. According to Johannes Kupang, the number of sufferers of chronic kidney disease in January-June 2023 was 44 people at RSUD W.Z.Johanes Kupang. This research method is included in the analytical descriptive research category which uses a cross-sectional framework. Findings Specifically, participants' energy expenditure (63.2%) fell into the "severe deficit" category. The majority of participants' protein intake (68.2%) fell into the severe protein deficiency category. The majority of patients undergoing hemodialysis were over 2 years old and included 54.5% of the sample. The nutritional status of most respondents (77.3%) was classified as normal. The results of the chi-square test showed that there was no significant relationship between the duration of hemodialysis and nutritional status (P=0.550). Based on the research results, the results of the chi-square test showed that in chronic stable patients there was no significant relationship between energy intake and nutritional status (P = 0.458), and protein intake and nutritional status also did not show a significant relationship. (P = 0.267) between conditions. RSUD Dr. W.Z. Johanes Kupang.